Multifunctional Contribution of the Inflated Fruiting Calyx: Implication for Cuticular Barrier Profiles of the Solanaceous Genera Physalis, Alkekengi, and Nicandra - de Souza, Aline Xavier; Riederer, Markus; Leide, Jana (Frontiers in Plant Science, 2022)
1. Pivotal barrier properties of the hydrophobic plant cuticle covering aerial plant surfaces depend on its physicochemical composition. Among plant species and organs, compounds of this boundary layer between the plant interior and the environment vary considerably but cuticle-related studies comparing different organs from the same plant species are still scarce. 2. Thus, this study focused on the cuticle profiles of Physalis peruviana, Physalis ixocarpa, Alkekengi officinarum and Nicandra physalodes species. Inflated fruiting calyces enveloping fruits make Physalis, Alkekengi and Nicandra highly recognisable genera among the Solanoideae subfamily. Although the inflation of fruiting calyces is well discussed in the literature still little is known about their post-floral functionalities. 3. Cuticular composition, surface structure and barrier function were examined and compared in fully expanded amphistomatous leaves, ripe astomatous fruits, and fully inflated hypostomatous fruiting calyces. Species- and organ-specific abundances of non-glandular and glandular trichomes revealed high structural diversity, covering not only abaxial and adaxial leaf surfaces but also calyx surfaces, whereas fruits were glabrous. 4. Cuticular waxes, which limit non-stomatal transpiration, ranged from < 1 μg cm-2 on P. peruviana fruiting calyces and N. physalodes fruits to 22 μg cm-2 on P. peruviana fruits. Very-long-chain aliphatic compounds, notably n-alkanes, iso- and anteiso-branched alkanes, alkanols, alkanoic acids and alkyl esters, dominated the cuticular wax coverages (≥ 86%). Diversity of cuticular wax patterns rose from leaves to fruiting calyces and peaked in fruits. The polymeric cutin matrix providing the structural framework for cuticular waxes was determined to range from 81 µg cm-2 for N. physalodes to 571 µg cm-2 for A. officinarum fruits. 5. Cuticular transpiration barriers were highly efficient, with water permeabilities being ≤ 5 × 10-5 m s-1. Only the cuticular water permeability of N. physalodes fruits was 10 × 10-5 m s-1 leading to their early desiccation and fruits that easily split, whereas P. peruviana, P. ixocarpa and A. officinarum bore fleshy fruits for extended periods after maturation. Regarding the functional significance, fruiting calyces establish a physicochemical shield that reduces water loss and enables fruit maturation within a protective microclimate, and promotes different seed dispersal strategies among plant species investigated.